Analisis Yuridis Perlindungan Hukum terhadap Lender sebagai Akibat dari Gagal Bayar yang Dilakukan oleh Borrower pada Fintech P2P Lending - Muhammad Iqbal Fauzan (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
The rapid development of information technology has an impact on the development of financial services with the presence of Peer-to-Peer (P2P) Lending Financial Technology. The presence of P2P Lending has created its own legal complexities in relation to the legal relationship between lender and borrower and risk mitigation efforts, especially the risk of default without specific collateral. This research aims to analysis the legal relationship between Lender and Borrower and the legal protection for Lender in the event of default risks in the implementation of P2P Lending in Indonesia using a normative legal approach. The results of the research indicate that the legal relationship between lender and borrower is a general loan agreement involving a P2P lending platform as an intermediary between lender and borrower. POJK No. 10/POJK.05/2022 plays an important role as a regulation that ensures risk mitigation in the implementation of P2P lending, including the obligation of operators to transfer funding risks to third parties, which has been implemented by PT Amartha Mikro Fintek in collaboration with PT Jaminan Kredit Indonesia (Persero) to provide guarantee facilities for P2P Lending services to ensure legal protection for Lenders.